Can thermoregulatory traits and evolutionary history predict climatic niches of thermal specialists?. (25th March 2022) - Bujan, Jelena; Ollier, Sébastien; Villalta, Irene; Devers, Séverine; Cerdá, Xim; Amor, Fernando; Dahbi, Abdallah; Bertelsmeier, Cleo; Boulay, Raphaël
Abstract: Aim: Predictions of future species distributions rest on the assumption that climatic conditions in the current range reflect fundamental niche requirements. So far, it remains unclear to what extent this is true. We tested if three important factors determining fundamental niche—ecophysiology, morphology and evolutionary history—can predict the realized niche, using thermal specialist ants. They are suitable model organisms because their body temperature, metabolism and fitness are closely tied to the habitat temperatures. Location: Iberian Peninsula and Maghreb. Time period: 2013–2015. Major taxa studied: Ants (Hymenoptera:Formicidae). Methods: We measured heat tolerance, chill coma recovery, body size and phylogenetic relationships in 19 desert specialist ants in the genus Cataglyphis to test if these important determinants of fundamental niches are good predictors of species realized niches. We modelled species climatic niches using 19 bioclimatic variables from WorldClim for recorded occurrence of each species. Results: None of the determinants of the species' fundamental niche were linked to their realized climatic niche, modelled using species distribution models. However, both heat tolerance and chill coma recovery were highly correlated with body size and all three thermoregulatory traits were phylogenetically constrained, suggesting they reflect fundamental requirements of each species. Main conclusions: Our results challenge the basic assumption of climatic niche modelling, that the realized niche can be used as a proxy for determining fundamental niche requirements. These findings are particularly concerning for studies that use the species' current realized niche to predict their responses to climate change.